Transformasi Community Policing dalam Pelayanan Publik: Analisis Peran, Inovasi dan Tantangan Kepolisian di Kota Padang - Mutia khairunnisa; Ratu Cutressa; Elsaata Putri; Dea Artika Sari; Jumiati Jumiati; Boni Saputra (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2025)
This research examines the public policy process in local government organizations in Padang City, focusing on the challenges and role of the Police in fulfilling community services in Padang City. In addition, this research also describes the real practices and challenges faced during the process. The method used was a qualitative approach, including an interview with one of the police officers. This research found that the community service process carried out by the police faces various challenges or obstacles, both in terms of the demands of diverse community needs, lack of community awareness and participation, and the mindset of the community who are still fixated on the bad side of the police.